(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The present study was conducted with the aim of investigating the B.M.I. status of Lawyers of 25-35, 36-45, and 46-55 years age group. The data were collected from 300 lawyers having membership of different Elite health clubs situated in Delhi, Gurugram, and Chandigarh. The selection of the subjects were made in purposive manner. The subjects volunteered to the research study after knowing the objectives of the study. Their B.M.I. scores were calculated with the help of formula weight in Kilogramheight in meter2. After collection of data it was analyzed with the help of SPSS software. Two Way ANOVA technique was used for the assessment of significant difference amongst selected age groups and professions. The level of significance was set at 0.05 for all the statistical analysis. The results of the study reveals that 25-35 years age group and 36-45 years age group do not differ from each other significantly. 25-35 and 46-55 years of age group differs from each other significantly. Age group 36-45 shown the least B.M.I. score amongst all the groups which is theoretically better and this group mean was significantly different than other two groups.